2011
DOI: 10.1007/s10549-011-1516-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on receipt of adjuvant chemotherapy for breast cancer in the National Comprehensive Cancer Network (NCCN) centers

Abstract: Disparities in the receipt of adjuvant chemotherapy for early stage breast cancer is an important factor influencing mortality. We investigated whether greater body mass index (BMI) decreases receipt of adjuvant chemotherapy among women with operable breast cancer. In the NCCN breast cancer outcomes database, we identified women age ≤70 with newly diagnosed stage I, II or III breast cancer between 1997 and 2007, for whom use of adjuvant chemotherapy was classified as either standard-of-care or discretionary ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
6
1
2
Order By: Relevance
“…This percentage is slightly higher than the 31% overweight reported in a study including 9,527 patients diagnosed with breast cancer from 1997 to 2007 at participating centers of the National Comprehensive Cancer Network 21 . A Korean study found differences in the BMI between East Asian and Western women 22 .…”
Section: Discussioncontrasting
confidence: 55%
“…This percentage is slightly higher than the 31% overweight reported in a study including 9,527 patients diagnosed with breast cancer from 1997 to 2007 at participating centers of the National Comprehensive Cancer Network 21 . A Korean study found differences in the BMI between East Asian and Western women 22 .…”
Section: Discussioncontrasting
confidence: 55%
“…Women with existing comorbid conditions are known to receive less extensive breast cancer treatment (43), and since chemotherapy is associated with weight gain (4447), the lack of weight gain or weight loss may be an indicator for treatment that is not the standard of care (48). Additionally, women with comorbid conditions at the time of breast cancer diagnosis are more likely to be subsequently hospitalized for chemotherapy toxicity, infection and fever, neutropenia, anemia, all of which increase the risk of weight loss (49) and decrease survival.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] There are concerns that obese women could potentially experience toxic effects if chemotherapy doses were based on their actual body weight. 43 It also has been suggested that diabetic women may receive less aggressive treatment because of their diabetes-related complications 11,46 ; 38% of the obese breast cancer cases were diabetic.…”
mentioning
confidence: 99%